Cidades e crianças: uma proposta de planejamento territorial no núcleo de Holanda em Santa Leopoldina/ES - Frassi, Lorena (2023)
Using as guide the following problem question “Is it possible for a given group of children to show interest, engagement and contribute to the territorial planning of the community in which they live?”, this research approached the themes of participatory territorial planning, the involvement and engagement of children in public policies – especially those that address territorial planning – and gamification as a facilitator in the development of proposals for the territory where they live. To meet the general and specific objectives outlined, an empirical research was carried out with a group of children aged between 10 and 12 years, students of the 6th and 7th year of the Municipal School of Early Childhood Education and Elementary School Alfredo Leppaus from the community of Holanda, in the municipality of Santa Leopoldina/ES. The activities carried out with the children were divided into three stages: freehand drawing, the use of the Minecraft geogame as a tool for the intervention and territorial planning stage and, finally, questions to evaluate the activities.